Cognitive Assessment Instrument Development for Learners with Special Needs in Inclusive Elementary Schools (Journal of Research and Educational Research Evaluation, 2022)
This research aimed to develop a cognitive assessment instrument for learners with special needs in inclusive elementary schools, focused on slow learners. The type of the research used is R&D (Research and Development) with the development model proposed by Borg & Gall. Sukmadinata modified the design from Borg & Gall in three main steps, that is (1) preliminary study; (2) product development; and (3) product testing. The subjects of this study were 3rd Grade students of SDN 14 Mulyoharjo. Research data obtained through interviews, observations and tests. The instrument developed was made in two question packages. Based on the result of the study, it was found that the assessment instrument aimed at inclusive elementary students was declared feasible. This is indicated by content validity validity, which was 0.80 to 1.00, the reliability between experts that resulted as much as 0.796 is categorized as good, and the reliability of large-scale test instruments belong to the very reliable category as indicated by the Kuder Richardson (KR) 20 value of 0.983 and 0.976. The equivalence test was carried out using the mean equalizing method and yielded a value of 8.71. Therefore, it can be concluded that the assessment instrument intended for students in inclusive elementary schools has met the specified criteria values so that it is feasible to use. The implication of the assessment instrument is that it can facilitate and assist teachers in inclusive primary schools in carrying out assessments.